Thematic Analysis of Men’s Roles in Gender Justice According to the Quran: Domestic and Public Perspectives - Salam, Mohammad Tohir; Nasution, Rika Amelia; Siregar, Ahmad Dairobi (Arba: Jurnal Studi Keislaman, 2026)
Gender justice studies in Quranic studies tend to focus on women as the parties affected by inequality. In contrast, the normative construction of men as active subjects forming just relations has not been systematically studied within a comprehensive thematic framework. This gap has implications for the limited conceptual formulation of gender responsibility from a Quranic perspective. This study aims to formulate a normative-analytical framework on the role of men in gender justice in the domestic and public spheres through a critical thematic reinterpretation of the Quranic text. This research is a literature study with a thematic interpretation approach (mawḍūʻī) based on critical gender analysis, using verse selection criteria related to leadership, family responsibilities, social relations, and moral accountability, and referring to classical and contemporary interpretations for comparative analysis and conceptual synthesis. The results of the study show four integrative dimensions: first, the principle of moral responsibility as an ontological foundation that positions men as ethical agents bound by the mandate of justice; second, domestic relational justice that emphasizes partnership, protection, and respect based on mutuality, not hierarchical superiority; third, public social accountability that constructs leadership as an ethical-transformative function for the collective good; fourth, domestic-public integration as a coherent model of gender responsibility that rejects role dichotomy. These findings broaden the discourse on gender interpretation by shifting the focus from the victim narrative to the construction of men’s normative responsibility, and they provide a conceptual foundation for developing equality policies and practices grounded in Quranic values.